Coco-granola manufacturing plant - Cruz, Rolando Aseron; Daco, Glenda; Jaurigue, Ratzeburg Regis; Mansueto, Locedie Ancog (College of Engineering, 1997)
Product: Coco-granola bars -- Brand name: "Fabulous" -- Volume: 30,357,140 bars per year -- Capacity: 850 MT per year -- Selling price: Php 4.60 per bar -- Retail price: Php 6.00 per bar -- Total capital investment: Php 30,924,000 -- Total product cost: Php 98,351,000 -- Return on investment: 25% -- Payback period: 3.7 years -- Plant location: Canlubang, Calamba, Laguna